Serum Electrolytes and Their Combined Effect on Hyperuricemia among Type 2 Diabetic Patients: Serum Electrolytes and Hyperuricemia among Type 2 Diabetic Patients - Begum, Nasreen; Rafi, Uzma; Khalid, Sidra; Hameed, Sajid; Iqbal, Neelam; Faridi, Tallat Anwar; Ullah, Rana Hammad (Pakistan BioMedical Journal, 2025)
Hyperuricemia (HU) is a metabolic and kidney dysfunction that is rapidly prevailing. To compare the diabetic, gender, and age-based response of magnesium and potassium in patients with diabetes mellitus (DM) type 2. Objectives: To compare the diabetic, gender, and age-based response of magnesium and potassium in patients with diabetes mellitus (DM) type 2. Methods: It was a randomized controlled trial (single-blinded) conducted on 290 patients. Four groups were formed: T1 (control), T2 (Magnesium), T3 (Potassium), and T4 (Magnesium + Potassium). Supplements were given for a period of two months. Blood samples from subjects were taken before (phase I) and after (phase II) the supplements. Unpaired t-test and multivariate Analysis of Variance (MANOVA) were applied. Results: Among 290 participants, 195 were female (67.2%) and 95 male (32.7%), with 159 (54.8%) of all participants in the age range of 46-65 years. The mean uric acid levels dropped from 5.5 mg/dL to 4.6 mg/dL after medication intervention. Significant differences in BSF/R, HbA1c, and uric acid levels were reported between phase I and phase II; p-values <0.001, 0.0025, and 0.04, respectively. MANOVA determined that T3 was highly significant with respect to gender (0.005) and T4 with respect to age (0.01). While the control group showed the largest absolute drop in uric acid, potassium supplementation (T3) demonstrated a consistent and statistically significant reduction relative to baseline and across gender groups. Conclusions: Potassium substantially plays an effective role in lowering the BSF/R and uric acid levels of T2DM patients and is controlled by gender.